Natural disasters and energy innovation: unveiling the linkage from an environmental sustainability perspective - Ahmed, Nihal; Ore Areche, Franklin; Saenz Arenas, Esther Rosa; Cosio Borda, Ricardo Fernando; Javier-Vidalón, Jorge L.; Silvera-Arcos, Susan; Ober, Józef; Kochmańska, Anna (Frontiers in Energy Research, 2023)
Natural disasters, characterized by their escalating frequency and intensification, fueled relentlessly by the inexorable forces of climate change, unambiguously underscore the urgent need to reassess our built environments and meticulously revise infrastructure design to withstand the unforgiving onslaught of these extreme events, thereby demanding concerted attention and unwavering dedication from policymakers and academic researchers to navigate this formidable predicament. The current study delves into the exploration of how natural disaster impact the course of energy technology evolution. To achieve this, This investigation uses panel data from 1990-2020 and sophisticated econometric analyses to model the effect of calamities on energy technology advancement across BRICS countries. Rigorous empirical methodologies lend credibility regarding the observed detrimental impact of disasters on innovation.the investigation leverages panel data methodologies spanning from 1990 to 2020, involving BRICS countries. The preliminary findings of the investigation suggest that natural disasters potentially exert a markedly detrimental effect on energy technology innovation. This influence is not merely confined to the year of the disaster occurrence but persistently lingers for the subsequent four-year period. Moreover, the adverse impacts of such environmental upheavals on energy evolution seem to be mitigated by various factors. These include robust economic growth, government stability, interpersonal globalization, financial openness, trade openness, and the expansion of social globalisation. Adding further dimension to this research is the understanding that epidemics have the most pronounced negative implications on energy innovation. Concluding on a nuanced note, the study underscores a significant inverse relationship between natural disasters and low-carbon energy innovation. Interestingly, however, there is no discernible correlation when it comes to non-low carbon energy innovation. In a nutshell, this research presents a potential reference guide for policymakers, illuminating pathways to enhance the degree of energy innovation while tackling natural disasters and ensuring environmental sustainability.